Depositional setting, provenance, and tectonic-volcanic setting of Eocene–Recent deep-sea sediments of the oceanic Izu–Bonin forearc, northwest Pacific (IODP Expedition 352). Issue 15 (18th November 2018) - Robertson, Alastair H. F.; Kutterolf, Steffen; Avery, Aaron; Baxter, Alan T.; Petronotis, Katerina; Acton, Gary D.; Carvallo, Claire; Schindlbeck, Julie C.
ABSTRACT: New biostratigraphical, geochemical, and magnetic evidence is synthesized with IODP Expedition 352 shipboard results to understand the sedimentary and tectono-magmatic development of the Izu–Bonin outer forearc region. The oceanic basement of the Izu–Bonin forearc was created by supra-subduction zone seafloor spreading during early Eocene (c. 50–51 Ma). Seafloor spreading created an irregular seafloor topography on which talus locally accumulated. Oxide-rich sediments accumulated above the igneous basement by mixing of hydrothermal and pelagic sediment. Basaltic volcanism was followed by a hiatus of up to 15 million years as a result of topographic isolation or sediment bypassing. Variably tuffaceous deep-sea sediments were deposited during Oligocene to early Miocene and from mid-Miocene to Pleistocene. The sediments ponded into extensional fault-controlled basins, whereas condensed sediments accumulated on a local basement high. Oligocene nannofossil ooze accumulated together with felsic tuff that was mainly derived from the nearby Izu–Bonin arc. Accumulation of radiolarian-bearing mud, silty clay, and hydrogenous metal oxides beneath the carbonate compensation depth (CCD) characterized the early Miocene, followed by middle Miocene–Pleistocene increased carbonate preservation, deepened CCD and tephra input from both the oceanic Izu–Bonin arc and the continental margin Honshu arc. The Izu–Bonin forearc basement formed in a near-equatorial setting, with late Mesozoic arc remnants to the west. Subduction-initiation magmatism is likely to have taken place near a pre-existing continent–oceanic crust boundary. The Izu–Bonin arc migrated northward and clockwise to collide with Honshu by early Miocene, strongly influencing regional sedimentation.